Global trade and poor nations the poverty impacts and policy implications of liberalization - Hoekman, Bernard M., 1959-; Olarreaga, M. (Marcelo) (Brookings Institution Press, 2007)
"Assesses the impact of reformed trade policies on the poorest of the poor from a spectrum of poor nations across different regions. Provides guidelines regarding the likely impacts of a global trade reform, utilizing a methodology that combines information to capture effects at the macro level and in individual households"--Provided by publisher.